2011
DOI: 10.1186/1476-511x-10-173
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profile of polyunsaturated fatty acid treated glioma cells reveal apoptosis-specific expression changes

Abstract: BackgroundPolyunsaturated fatty acids (PUFAs) such as γ-linolenic acid (GLA), arachidonic acid (AA) and docosahexaenoic acid (DHA) have cytotoxic action on glioma cells.ResultsWe evaluated the cytotoxic action of GLA, AA and DHA on glioma cells with specific reference to the expression of miRNAs. Relative expression of miRNAs were assessed by using high throughput nanocapillary real-time PCR. Most of the miRNA target genes that showed altered expression could be classified as apoptotic genes and were up-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 23 publications
(21 reference statements)
7
44
0
1
Order By: Relevance
“…Faragó et al demonstrated the effect of PUFAs, including DHA, on the involvement of the microRNA profile in apoptosis-specific changes in treated glioblastoma cell lines. 8 In their study, these investigators observed similar findings with the administration of temozolomide alone.…”
supporting
confidence: 72%
“…Faragó et al demonstrated the effect of PUFAs, including DHA, on the involvement of the microRNA profile in apoptosis-specific changes in treated glioblastoma cell lines. 8 In their study, these investigators observed similar findings with the administration of temozolomide alone.…”
supporting
confidence: 72%
“…Therefore, although the two conditions shared a similar miRNA expression pattern, 69 miRNAs (51 upregulated and 18 downregulated in aMEM) deviated from linearity with 4-fold or higher differential expression (Table 3). Of note, two miRNA that were demonstrated to be repressed by different PUFA (including linoleic acid) in glioma cells (miR-143 and miR-125b; Faragó et al, 2011) showed an identical pattern in CBMSC grown in SPE-IV, that was able to reduce both miR-143 (16.80 fold) and miR-125b (4.23 fold) with respect to aMEM. Moreover, our results are also in agreement with those obtained in the work of Parra and colleagues that showed, upon conjugated linoleic acid treatment in mice, repression for miR-143 and induction of miR-221/222 as we observed in SPE-IV (5.55 and 14.29 fold) (Parra et al, 2010).…”
Section: Identification Of Unique Mirna Signatures and Target Analysismentioning
confidence: 93%
“…Then we decided to investigate on a molecular level the macroscopic changes previously described since differences in medium supplements, as fatty acids, have been recently shown to modulate different parameters like miRNA expression (Parra et al, 2010;Faragó et al, 2011). So, we performed a miRNA expression profiling monitoring the amount of 704 mature miRNA using qRT-PCR arrays.…”
Section: Identification Of Mirna Expression Profiles In Amem and Spe-mentioning
confidence: 99%
“…We showed that AA reduces the expression of these genes by regulating their promoter activity in a transcriptional manner. Several studies have demonstrated that AA reduces the expression of apoptosis-related proteins, including the known antiapoptotic protein BCL2 (20,63,64). However, no studies have linked AA or other PUFAs to the antiapoptotic genes BFL1/A1 and 4-1BB.…”
Section: Discussionmentioning
confidence: 99%